2010
DOI: 10.1021/ct900670a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Hydrolysis of Pentameric Aluminum Complexes

Abstract: Static quantum chemical calculations and Car-Parrinello molecular dynamics (CPMD) simulations were used to investigate the structural characteristics and the stability of pentameric aluminum clusters in both gas phase and aquatic environments. The accuracy of several generalized gradient approximation (GGA) and hybrid exchange-correlation functionals were tested with and without empirical van der Waals corrections to ensure the accuracy of the selected methods. Conformational analysis was performed for experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 81 publications
4
24
1
2
Order By: Relevance
“…The study of Al toxicity to algae is complicated by the chemical properties of Al itself, its low solubility and the interactions with counter ions such as phosphates, sulphates, chlorides and carbonates [32]. Aluminium forms different species in the media depending strongly on the pH, temperature and concentrations of other ions [32,33]. Although according to some authors these Al concentrations found in our treatments are high enough to inhibit Chlorella growth [32,34,35] others show high tolerance to Al [32,36,37,38,39].…”
Section: Figs 3 and 4 Andmentioning
confidence: 77%
See 1 more Smart Citation
“…The study of Al toxicity to algae is complicated by the chemical properties of Al itself, its low solubility and the interactions with counter ions such as phosphates, sulphates, chlorides and carbonates [32]. Aluminium forms different species in the media depending strongly on the pH, temperature and concentrations of other ions [32,33]. Although according to some authors these Al concentrations found in our treatments are high enough to inhibit Chlorella growth [32,34,35] others show high tolerance to Al [32,36,37,38,39].…”
Section: Figs 3 and 4 Andmentioning
confidence: 77%
“…Generally, Al is most toxic to algae under slightly acidic conditions (pH~6.0) and almost all the studies of the effects of Al on Chlorella growth found in the literature were performed at acidic pH [32]. However, in our study the initial and final pH of the cultures is in the range 9.0-7.7, conditions in which predominates the aluminate anion [Al(OH) 4 ] − , Al(OH) 3 as very insoluble gibbsite and possible small concentrations of [Al(OH) 5 ] 2− [32,33]. Until now the toxic effects of aluminate anion on green algae and specifically on Chlorella sp.…”
Section: Figs 3 and 4 Andmentioning
confidence: 79%
“…This may be due to the fact that lime solution acts as a pH controller and, with increase in CaO dose, the pH as well as the alkalinity of the solution also increases. The higher the pH, the higher the negative charges had by the solution and the more aluminium coagulants are needed to neutralize and precipitate the charged species [24]. In addition, the demand for alum increases with increase of alkalinity.…”
Section: Optimum Dosage Of Coagulant Aidmentioning
confidence: 99%
“…В качестве исходной слоистой матрицы чаще всего используют монтмориллонит, а самыми рас-пространенными интеркалирующими агентами явля-ются поликатионы алюминия, образующиеся в водных растворах солей этого металла. В частности, наиболее популярна интеркаляция ионов [Аl 13 Несмотря на то, что гидролиз солей алюминия яв-лялся объектом исследования на протяжении многих десятилетий, эти исследования продолжаются и в на-стоящее время с целью обнаружения с помощью сов-ременных физических методов (масс спектрометрия с ионизацией электрораспылением [5][6][7][8] 3 , служащих связующим мостиком между А1 13 [9] (рис.1). Важно отметить, что согласно результатам [12] комплексы Al 30 , в отличие от А1 13 , активны в спектрах флуоресценции: наблюдаются интенсивные полосы в ближних ИК и УФ областях спек-тра.…”
Section: Introductionunclassified